Previously unknown diversity: the marine sponge (Porifera) fauna from Rio Grande do Norte State, NE Brazil - Praxedes, Rayran Araújo; Rabelo, Emanuelle Fontenelle; Cavalcanti, Thaynã; Brandão, Simone Nunes; Pinheiro, Ulisses; Albuquerque, Cristiano Queiroz De (Zootaxa, 2024)
The Brazilian spongiofauna is still one of the least known worldwide, and the Northeastern region of Brazil is the one with the greatest recorded diversity. Previous studies on sponges in the Rio Grande do Norte State focused on deeper regions of the Potiguar Basin and oceanic islands, lacking any records from intertidal environments. The present study aimed to investigate the biodiversity of marine sponges from two beaches on the northern coast of Rio Grande do Norte. The specimens were collected in intertidal beachrocks of Baixa Grande and Ponta do Mel beaches (Areia Branca, RN) quarterly between August 2018 and May 2019, using the active search method for 2 hours during low tide. We identified 19 species belonging to the Demospongiae class, four taxa were considered dominant and six were considered rare according to the sampling period. Our study considerably improved the knowledge of the spongiofauna for the Rio Grande do Norte State, with six new taxa occurrences: Placospongia sp., Dysidea robusta, Haliclona (Reniera) manglaris, Haliclona (Reniera) tubifera, Haliclona (Soestella) caerulea and Amorphinopsis atlantica.